Striking Balance in Democratic Governance: The Battle for Control between the Administrative and Legal Branches - Yaron Katz (RIRAI Publisher, 2024)
The perception of the role of the court in democracy is a complex and frequently debated aspect of political systems. It involves how individuals, institutions, and society at large view the function, powers, and responsibilities of the judiciary within the broader democratic framework. The role of the court is deeply intertwined with the principle of separation of powers, which delineates distinct functions for the legislative, executive, and judicial branches. However, the perception of the court's role in shaping and influencing public policies is a subject of discussion, since the effectiveness of the court in a democracy is closely linked to public trust and legitimacy. Prominent researches argue that the court should actively contribute to policy development, while others believe that its primary function should be limited to interpreting and applying existing laws. As a result, debates often arise over the extent to which the court should exercise its power of judicial review. A perceived lack of impartiality, independence, or transparency can erode public trust, impacting the credibility of the court's decisions and its overall role in democratic governance. While courts have the authority to render judgments, their ability to enforce decisions and ensure compliance with the rule of law relies on the cooperation of other branches and societal actors. The research highlights contrasting viewpoints on the court's responsibility in safeguarding constitutional principles through the rejection of legislative and executive actions that contradict constitutional norms. The core issue revolves around the significance of this and whether it presents a potential threat by enabling the court to supersede decisions made by duly elected representatives of the public.